Sustainable Drainage Practices in Spain, Specially Focused on Pervious Pavements - Jorge Rodriguez-Hernandez (Water, 2013)
The Spanish climate is full of contrasts, with torrential rains and long droughts; under these conditions, appropriate water management is essential. In Spain, until the end of the twentieth century, water management and legislative development lagged behind other more developed countries. Nowadays, great efforts are being made to reverse this situation and improve both water management and legislation in order to control the two main problems related to stormwater management in cities: floods and diffuse pollution. In this context, Sustainable Urban Drainage Systems (SUDS) were developed as the main solution to these problems. The study of these techniques started in the 1970s in the USA, but they were not studied in Spain until 1993 when the University of Cantabria and CLABSA started to look into solutions for stormwater management. After 20 years of research and application, sustainable drainage in Spain is still behind other countries in spite of the efforts to change this situation, notably by the University of Cantabria with 10 years of experience in these techniques, mainly regarding pervious pavements, where more than 13 related research projects have been carried out. The future challenges focus on the application of pervious pavements for Urban Hydrological Rehabilitation.